CHẾ TẠO VẬT LIỆU NANO γ-Fe2O3/CÁT THẠCH ANH HẤP PHỤ ASEN, SẮT VÀ MANGAN - Đại, Lưu Minh; Tố Loan, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
The nanosized γ-Fe2O3 coated sand was synthesized and used in the arsenic, manganese and iron adsorption. Gel was prepared from polyvinyl alcohol (PVA) and iron nitrate at temperature of solution 80oC with molar ratio PVA/metal = 3/1. Then soaking the gel with sand of size from 0.5 to 1.0 mm, drying and calcinating at 250oC for 2 hours  to obtain the nanosized g-Fe2O3 coated sand. The nanosized γ-Fe2O3 coated sand material of size from 0.5 to 1.0 mm yielded maximum sorption capacity of 1.71 mg/g for As(III);  1.89 mg/g for As(V), 2,93 mg/g for manganese and  4.00 mg/g for iron according to the Langmuir isotherm.